2011
DOI: 10.1111/j.1365-2591.2011.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reconstructed images with different voxel sizes of acquisition in the diagnosis of simulated external root resorption using cone beam computed tomography

Abstract: In the diagnosis of simulated external root resorption with the Classic i-CAT CBCT unit, images acquired with 0.30 mm voxel size and reconstructed with 0.25 mm voxel size provided the best protocol with a lower radiation dose than the 0.25 mm voxel size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
2
28
0
2
Order By: Relevance
“…In one of them, although images were generated using diverse voxel sizes, this parameter was not assessed and interpreted in the results, which referred to other parameters (e.g., unit, FOV, and section thickness) [1]. One study tested various voxel sizes used to acquire the images (0.30 and 0.25 mm) but reconstructed the images using the same final resolution (0.25 mm), neglecting a direct comparison of voxel size [14]. The other studies were excluded because no gold standard was employed [15,16] or because the evaluation was merely subjective of image quality [7].…”
Section: Review Search Resultsmentioning
confidence: 99%
“…In one of them, although images were generated using diverse voxel sizes, this parameter was not assessed and interpreted in the results, which referred to other parameters (e.g., unit, FOV, and section thickness) [1]. One study tested various voxel sizes used to acquire the images (0.30 and 0.25 mm) but reconstructed the images using the same final resolution (0.25 mm), neglecting a direct comparison of voxel size [14]. The other studies were excluded because no gold standard was employed [15,16] or because the evaluation was merely subjective of image quality [7].…”
Section: Review Search Resultsmentioning
confidence: 99%
“…3,5 No randomized controlled trials were found during the literature search. Of the 22 other full-text articles included in the review, 10 studies looked at the effect of altering the current, [19][20][21][22][23][24][25][26][27][28] 6 studies at altering kilovoltage 19,20,23,24,26,27 and 18 studies at altering exposure time factors 19,21,22,[24][25][26][27][29][30][31][32][33][34][35][36][37][38][39] (some studies looked at more than one exposure parameter, so this total equals .20 studies). One study 40 investigated the combined effect of current and exposure times on image quality by altering mAs values.…”
Section: Resultsmentioning
confidence: 99%
“…After that, the full texts of the reserved 31 citations were obtained and evaluated per the inclusion criteria. Finally, 15 studies were included in the systematic review [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ( Figure 1). Among the enrolled studies, nine studies reported the diagnos- tic efficacy of CBCT with a sample size of 1097 suspected ERR sites, and 11 reported information of PR with a sample size of 1072 sites (five studies focused on both modalities).…”
Section: Description Of Included Studiesmentioning
confidence: 99%